Factors Affecting Digital Financial Literature on Batik SMEs in Banyumas Regency - Naufalin, Lina Rifda; Tohir, Tohir (Economic Education Analysis Journal, 2022)
This study aimed to analyze the factors that influence the level of digital financial literacy in Batik SMEs in Banyumas Regency in terms of age, education level, and income level. The object of this research was the Batik SMEs, a member of the Berkah Rindang Kinasih Cooperative, which consists of two plasmas with a total of 24 Batik SMEs. The research method used quantitative method with multiple regression analysis Partial T Test and Simultaneous F Test. The data collection technique was in the form of a questionnaire on digital financial literacy variables. The results of the study were training did not partially affect the digital financial literacy variable, motivation did not partially affect the digital financial literacy variable, age did not partially affect the digital financial literacy variable, education level had no effect partially on the digital financial literacy variable and the level of income did not partially affect the digital financial literacy variable. However, the variables of training, motivation, age, education level, and income level simultaneously or simultaneously affected the Digital Financial Literacy variable.